2018
DOI: 10.1111/joid.12119
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Interior Designers’ Research Utilization Strategies and Information–Seeking Behaviors

Abstract: Research findings that remain unknown to design practitioners stand little chance of improving their design processes or project outcomes. The research utilization gap is evident from both the perspectives of scholars and design practitioners. While design scholars have long lamented practitioners' apparent indifference toward scholarly research, some interior designers and architects attribute their apathy to irrelevance. The few strategies that have been offered to reconcile this divide largely remain untest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 62 publications
(109 reference statements)
1
11
0
Order By: Relevance
“…Considering the above, it is not surprising that the lack of available information regarding the state-of-the-art SIAD practices, successful examples, and local sustainable material databases are regarded as crucial deterrents. However, recent studies on the designers' information processing preferences reported that designers do not fully utilize all research strategies and rarely use findings of academic research [82]. Consequently, the importance of appropriate education and training-in this case with respect to research strategies-is further amplified.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the above, it is not surprising that the lack of available information regarding the state-of-the-art SIAD practices, successful examples, and local sustainable material databases are regarded as crucial deterrents. However, recent studies on the designers' information processing preferences reported that designers do not fully utilize all research strategies and rarely use findings of academic research [82]. Consequently, the importance of appropriate education and training-in this case with respect to research strategies-is further amplified.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 study found only 30.9% of interior designers were extremely likely to practice EBD, though over 70% gathered project-related information. Survey results also discovered that nearly one-third of respondents gathered information to confirm existing beliefs (Huber, 2018a), suggesting confirmatory bias (Trope & Liberman, 1996).…”
Section: Constraints On Idssmentioning
confidence: 99%
“…Through extensive teaching experience in biophilic design, the author has noted that one of the most consistent struggles for students is a lack of creative synthesis-in other words, a disconnect between the analytical information-gathering process and the ability to bring these concepts together to create a coherent design product (Huber, 2018). The overall design concept and communicated meaning is central to achieving the goals of biophilic design.…”
Section: Biophilic Design Educationmentioning
confidence: 99%